Proto-industrialization in the mid-nineteenth-century Balkan countryside: textile manufacturing in villages of Plovdiv - Öncel, Fatma. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2012., 2012)
This study analyzes the rural manufacturing in the mid-nineteenth century Ottoman Balkans. Woollen-textile manufacturing in three villages of Plovdiv; Karlova, Kalofer and Sopot are examined for this purpose. The thesis focuses on the conditions of the emergence of the rural industries and the organization of the manufacturing process. This study proposes that the proto-industrialization theses provide a useful approach for analyzing the emergence of the nineteenth-century Ottoman rural industries as well as the organization of labour and production. Based mainly on the Income Surveys ( Temettuat Defterleri), this study analyzes the textile sector in the selected villages through the extensive use of the qualitative and quantitative data, both at the macro and at the micro levels. The study mainly argues that the combination of proto-industrialization theses with the information derived from the Income Surveys hold a great capacity to explain the causes of rural putting-out economies. It shows that protoindustrialization in Plovdiv villages emerged out of the specific geographic and demographic features of the region. It also points out that land shortage and lack of sufficient agrarian income directly stimulated the emergence of the rural manufacturing in these villages. The analysis of the labour organization and the commercial networks demonstrates that textiles became the dominant economic activity of Plovdiv villages in the context of a merchant-led, market-oriented putting out system. It also asserts that, based on the degree of influence created by the merchants, there were different types of proto-industries in Plovdiv villages.|Keywords : Plovdiv, rural manufacturing, putting-out, proto-industrialization, Temettuat.
Keywords: Industrialization -- Plovdiv (Bulgaria); Plovdiv (Bulgaria) -- History.